Magnetic hardening of Sm2Fe17N3 by radiation damage - COEY, JOHN MICHAEL DAVID (American Physical Society, 1998)
Pinning type coercivity has been induced in large (?50?m) particles of Sm2Fe17N3 by irradiation with 5 GeV Pb56+ ions. Mossbauer spectroscopy is used to analyze the structure of the defects and estimate their volume. Magnetization measurements indicate that the induced defects are anisotropic in shape. A model of strong pinning by cylindrical defects is employed to deduce a defect radius of order 2 nm from the measured fluence dependence of the coercivity.
PUBLISHED
Keywords: Physics